Dance and music therapy and their effects on quality of life in Parkinson’s Disease: a case study - Pereira, Carolina Duarte; Agner, Heloisa Pallasi; Freitas, Aline de Souza (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 41 No 78 (2025): Publicação Contínua, 2025)
Introduction: The Parkinson Disease (PD) characterizes itself as an idiopathic, degenerative, progressive and chronic neural system disease, who also lowers the dopamine levels. It presents itself especially on the 55 to 65 years old age group. The most common symptoms are trembling, stiffness, bradykinesia, body and gait instability and LQ decrease. It is known that stimulus such as sounds, rhythms and dance improves the life quality of those who suffer from PD, with repercussions on march, perfecting cognitive skills such as motor adjustments and spacial memory. Objective: Comprehend the effects of dance and music over the quality of life of the carrier of the Parkinson Disease. Methods: It’s a quantitative case study, performed at Clínica de Fisioterapia da Unifil. The instruments used were: neurofunctional physiotherapist evaluation; TUG; Berg Balance Scale; Schawb and England Activities of Daily Living Scale; PDQ-39; UPDRS and MEEM. 12 sessions were held, 2 to 3 times a week, with a duration of 50 minutes, with classical ballet and Xote rhythms associated with motor therapy. At the end of the treatment, the physiotherapy re-evaluation was carried out. Results: The patient included in this study presented stage 2 on the HY Degree of Disability Scale, lower risks of fall due to good balance and gait improvement, didn’t change the ADV classification, showed more initiative in performing non-habitual activities and improvement on mobility and AVD. Article conclusions: All the objectives have been achieved and they corroborated with other studies already present in the literature.